2011
DOI: 10.1007/s10517-011-1474-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Isotonic Point of Incubation Medium For Two-Cell Mouse Embryo

Abstract: Osmolarity of Dulbecco's medium at which the volume of two-cell mouse embryo remained similar to that of intact embryo was determined. The method is based on comparison of kinetic curves describing the volume of embryonic cell in solutions of different osmolarity. The blastomere volume was measured by quantitative laser microtomography after fixed osmotic stress intervals. It was found that Dulbecco's saline with 125 mM NaCl solution is an isotonic solution for two-cell mouse embryo. This concentration corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although we used 370 mOsM medium here to obtain a maximum difference between development with and without glycine, a significant decrease in development was evident between 310 and 330 mOsM. This is nearer to the in vivo osmolarity of oviductal fluid, which has been measured to be ~300 mOsM [42][43][44], although calculations have indicated it may reach as high as 350 mOsM during early preimplantation embryo development [3]. This is supportive of a possible role for glycine in vivo, since relatively small increases in oviductal fluid osmolarity would have an impact on embryo development even at the lower values proposed for oviductal fluid.…”
Section: Discussionmentioning
confidence: 84%
“…Although we used 370 mOsM medium here to obtain a maximum difference between development with and without glycine, a significant decrease in development was evident between 310 and 330 mOsM. This is nearer to the in vivo osmolarity of oviductal fluid, which has been measured to be ~300 mOsM [42][43][44], although calculations have indicated it may reach as high as 350 mOsM during early preimplantation embryo development [3]. This is supportive of a possible role for glycine in vivo, since relatively small increases in oviductal fluid osmolarity would have an impact on embryo development even at the lower values proposed for oviductal fluid.…”
Section: Discussionmentioning
confidence: 84%
“…It was concluded that this fluid has an osmolality of about 290-300 mOsmol/ kg based, in part, on the osmolality at which zygotes did not shrink or swell beginning 1.8 min after they were placed in media of various osmolalities between 200 and 400 mOsmol/ kg. The same approach for two-cell embryos yielded a similar conclusion (Collins and Baltz, 1999;Pogorelova et al, 2011). Not considered, however, were initial changes in zygote and embryo volume from when they were in oviductal fluid (e.g., Figure 2 in Collins and Baltz, 1999) to when volumes were measured in media 1.8 min later ( Figure 3 in Collins and Baltz, 1999).…”
Section: Attempts To Measure Oviductal Fluid Osmolality May Have Expomentioning
confidence: 78%
“…Perhaps more importantly, when glycine is present in the medium, it protects against one-cell embryo shrinkage even in medium of 350 mOsmol/kg (Steeves et al, 2003). Hence, most of the data in Figure 1, and data reported elsewhere (Collins and Baltz, 1999;Pogorelova et al, 2011), were collected under non-physiological conditions (in particular, in the absence of extracellular glycine in the medium).…”
Section: Attempts To Measure Oviductal Fluid Osmolality May Have Expomentioning
confidence: 99%
“…It was possible that the lower osmolarity of the media that supported complete preimplantation development could have been explained by their mimicking a low osmolarity environment of early embryos in the oviduct in vivo. However, measurements of the osmolarity of oviductal fluid instead showed that it was similar to the osmolarity of the fluids surrounding most cells and to that of culture media in which embryo development was blocked, with a range of about 290–310 mOsM for mouse oviductal fluid (Collins & Baltz, 1999; Fiorenza et al, 2004; Pogorelova et al, 2011), a similar range in rat (Waring, 1976), and somewhat higher at 320 mOsM in pig (Li et al, 2007). Indeed, these values may actually be low.…”
Section: Role Of Osmolarity In Developmental Arrest Of Early Embryosmentioning
confidence: 99%